[Log-book of the Endeavour, February-September 1770] - Cook, James (Adam Matthew Digital, 1770)
Captain Cook's logbook for the Endeavour's journey around New Zealand and Australia during his first voyage of discovery. A supplementary draft to Add Mss 8959